ÉPOCA DE SEMEADURA, CARACTERÍSTICAS MORFOLÓGICAS E COMPONENTES PRODUTIVOS DE HÍBRIDOS DE CANOLA (Brassica napus L.) - Comin, Gustavo Rufatto (2017)
Canola is an oleaginous plant that has shown potential to cropping in Brazil, aiming mainly the production of vegetable oil and biodiesel at the period of autumn-winter. The objective of this work was to evaluated growth and yield variables of seven canola hybrids (Hyola 575 CL, Hyola 571 CL, Hyola 433, Hyola 50, Hyola 61, HLHT B4 and HLHT BM6 CL) that were submitted to five different sowing dates (from middle of February until middle of May), with nearly 21 days of interval, and two cropping years (2015 and 2016). The experimental design was randomized blocks with split-plot scheme, where the date of sowing was the main plots, and the hybrids was the subplots, and three replications. The yield components were evaluated after harvest and growth variables during the full flowering stage. A principal component analysis was made with the evaluated parameters. The sowing date had effect in most of evaluated variables (exception for dry matter). The yield, mass of a thousand grains and number of silica showed better performance when the hybrids were sown between the end of March and the beginning of May. The hybrids HLHT BM6 CL and HLHT B4 were in the group of best yield when sowed at the end of March in 2015 and middle of April 2016, respectively. In both years, the frost affected the yield performance of the plants sown between February and middle of March. Sowing at the end of March resulted in higher height, number of nodes and stem diameter of the hybrids. Among the Hyola hybrids, genotype 575 CL showed higher height and stem diameter at most sowing times. The duration of the cycle and the vegetative stage increased with the advancement of the sowing seasons in the two years, but the flowering period reduced from the sowing in April in 2015 and from March in 2016. The hybrids HLHT BM6 CL and HLHT B4 present better potential for early sowing. The main component analysis allowed to evaluate that the note of frost and temperature variables had the greatest influence on the yield of hybrids.